TATA LETAK ILUSTRASI DITINJAU DARI SEGI PROPORSIONAL ILUSTRASI PADA BUKU PENDAMPING TEMATIK TERPADU IPA JILID 1 SESUAI KURIKULUM 2013 TERBITAN ERLANGGA - Aulia Dwiningtyas Putri; Irene Mari Juli Astuti (Jurnal Ilmiah Publipreneur, 2014)
This research aims to describe the problem in the book layout related 2013 curriculum illustration that proportionate in terms of illustration. This research focuses on the Integrated Thematic Companion Book Vol. 1 IPA. The research method used is the method of library research, observation, and interviews. The results can be concluded that the main obstacle is the difficulty of inserting an illustration into the box the picture proportionally. The fix is to change the size/shape of the illustration through the program Adobe Illustrator or by changing the size of the picture box on the form/Adobe InDesign.